Photocatalytic removal of ibuprofen from water using CuO/g-C3N4 nanocomposite - Murendeni P. Ravele; Olalekan C. Olatunde; Opeyemi A. Oyewo; Damian C. Onwudiwe (Next Materials)
The rising prevalence of pharmaceutical pollutants particularly, non-steroidal anti-inflammatory drugs like Ibuprofen (IBU) in aquatic ecosystems presents a significant risk to both environmental integrity and public health. Therefore, the need to develop effective remediation technology is highly important since traditional technologies are not capable of dealing with this class of materials. In this study the efficiency of a CuO/g-C3N4 nanocomposite as a photocatalyst for IBU degradation is explored. The nanocomposite was synthesized through a straightforward precipitation and calcination method, followed by characterization utilizing XRD, TEM, SEM, and UV–vis techniques. The findings indicate that the establishment of an S-scheme heterojunction involving CuO and g-C₃N₄ markedly improves charge separation, diminishes recombination rates, and elevates photocatalytic efficiency. Under optimized conditions, the CuO/g-C₃N₄ nanocomposite demonstrated an impressive degradation efficiency of 85.63 %, surpassing that of pristine CuO and g-C₃N₄. The results highlight the importance of developing effective photocatalysts for the treatment of pharmaceutical wastewater, positioning CuO/g-C₃N₄ as a viable option for environmental remediation efforts. This study offers novel perspectives on the engineering of S-scheme heterojunctions and their prospective use in sustainable water treatment technologies.